(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the connection between psychology and foreign language education, focusing particularly on lyceum students in Uzbekistan. It argues that psychological knowledge is not only helpful but essential in improving students’ English language acquisition. The paper highlights three main psychological components—emotional intelligence, motivation, and self-awareness—as critical factors that significantly affect the learning process.